The impact of International Public Sector Accounting Standards (IPSAS) on financial reporting quality in public sector: case study Rushinga Rural District Council - Augusto, Scholastica (Midlands State University, 2018)
The main objective of this project was to examine the impact of International Public Sector Accounting Standards on financial reporting quality using a case of Rushinga Rural District Council. The major issue that gave rise to the research study across this area was the increased demand for high quality information by public sector stakeholders after the 2008 economic crisis that left public sectors with huge amount of debts. This study employed a qualitative research approach in answering the research questions. The information and data was gathered from both secondary and primary sources. Primary data was collected through the use of questionnaires and interviews .A targeted population of 33 respondents consisting of the management, internal auditors and relevant accounting staff from which a sample of 28 respondents was incorporated. The key findings of the study shows that the implementation of IPSAS in public sector reporting will result in quality reporting. The study results showed that the adoption of IPSAS in public sector reporting is being affected by implementation costs, the level of available technology and the training and skills required to adopt IPSAS. Moreover, the findings showed that the adoption of IPSAS in public sector will improve transparency and accountability of financial statements, relevance, comparability and reliability of financial statements but will not curb corruption in public sectors. The study found out that some African countries have completed the adoption process and the other countries are still in progress of adopting IPSAS in public sector reporting. The researcher recommended the IPSASB to keep on supporting public sectors with financial assistant so as to mitigate the implementation challenges, improved communication and there have to be an increased number in training programs for all stakeholders to improve the use of IPSAS in public sectors. The study concluded that there's need to undertake the only International Accounting Standard in public zone reporting as the researcher located out that it's miles prompted that the advantages will outweigh the fees of enforcing IPSAS in public sector reporting.